2010
DOI: 10.1155/2010/645193
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Detection of Internal Jugular Vein Thrombosis Secondary to Undiagnosed Benign Substernal Goiter

Abstract: Internal jugular vein thrombosis is a serious event with potentially fatal outcome, where the clinical symptoms may be vague or absent. This paper refers to a rare case where routine carotid Doppler ultrasound prior to coronary artery bypass grafting (CABG) and aortic valve replacement (AVR) in a 76-year-old man, incidentally revealed thrombosis of the right internal jugular vein. Thoracic CT demonstrated an underlying, large, benign substernal multinodular goiter, mainly involving the right lobe, causing comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Typically, patients with internal jugular vein thrombosis or obstruction present with transient facial oedema, with or without associated neck swelling. However, the majority of neck vein thrombosis present with subtle signs such as pain and swelling at the angle of the jaw [5,6]. e atypical presentation of internal jugular vein thrombosis in our patient has rendered the diagnosis difficult.…”
Section: Discussionmentioning
confidence: 84%
“…Typically, patients with internal jugular vein thrombosis or obstruction present with transient facial oedema, with or without associated neck swelling. However, the majority of neck vein thrombosis present with subtle signs such as pain and swelling at the angle of the jaw [5,6]. e atypical presentation of internal jugular vein thrombosis in our patient has rendered the diagnosis difficult.…”
Section: Discussionmentioning
confidence: 84%
“…Upper extremity DVT and pulmonary emboli (PE) caused by substernal thyroid goiters are rare, with only a handful of reported cases in the literature. [1][2][3]5 One explanation for the infrequency of thyroid goiter-induced upper extremity DVT and PE is that their chronic and indolent growth pattern allows for the development of collateral circulation that helps prevent venous stasis, and thus, formation of DVT and pulmonary embolism. 2,4 Additionally, large substernal goiters are uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Substernal thyroid goiters have been linked to the formation of deep vein thrombosis (DVT). [1][2][3] As a substernal thyroid goiter enlarges, its mass effect can compress surrounding structures in the thoracic outlet. More specifically, the axillosubclavian and internal jugular veins can become compressed against the first rib, sternum, strap muscles, and thyroid goiter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghatak et al presented a case of spontaneous pulmonary embolism, IJVT, and subclavian vein thrombosis in a patient with septic shock who was found to have factor V Leiden mutation and activated protein C resistance and was curiously reported to have dengue IgM positive [ 14 ]. Lønnebakken et al found an internal jugular vein thrombosis incidentally secondary to substernal goiter [ 15 ].…”
Section: Discussionmentioning
confidence: 99%